Advances in the genetics of acute lymphoblastic leukemia in adults and the potential clinical implications. Issue 10 (3rd October 2018) - Horowitz, Netanel A.; Akasha, Doaa; Rowe, Jacob M.
ABSTRACT: Introduction : Acute lymphoblastic leukemia (ALL) is a clonal disease of the hematopoietic system characterized by unique genetic characteristics. The significance of these genetic features has evolved over the past three decades. In the 1980s and 1990s, the primary interest was in excluding the Philadelphia chromosome; a finding more common in older adults which uniformly predicted for a rapidly fatal outcome. Areas covered : Over the past 15 years, much has evolved. Tyrosine kinase inhibitors completely changed the prognosis of Ph-positive ALL. In addition, the genetic characterization of Ph-negative ALL has significantly advanced through systematic progressive analyses of genetic data from large trial groups. These led to specific and more accurate prognostication, particularly at initial diagnosis. Expert commentary : These cytogenetic and molecular features will be reviewed in this paper and their ongoing significance will be critically analyzed in the era of minimal residual disease (MRD) determination, which has now superseded all the major known historic prognostic factors.